Intermittent fasting regulates gut microbiota and serum metabolome profiles in middle-aged mice fed high-fat diet - Ziru Li; Sufang Chen; Bingbing Yin; Jiacun Wei; Duofei Wang; Huoxiang Zhou; Zhi Sun (Nutrition & Metabolism)
Abstract Background Intermittent fasting (IF) has received wide attention as an effective diet strategy. Existing studies showed that IF is a promising approach for weight control, improving insulin sensitivity and reducing type 2 diabetes mellitus (T2DM) prevalence. Methods Twenty-eight 8-month-old male C57BL/6J mice were randomly divided into a normal control group (NC), a high-fat diet group (HFD) and an HFD + IF group. Body weight (BW) and food intake were monitored weekly. After 20 weeks, the intraperitoneal glucose tolerance test (IPGTT), oral glucose tolerance test (OGTT), and intraperitoneal insulin tolerance test (IPITT) were performed weekly in sequence. Fresh faeces were collected to examine changes in gut microbiota, and serum untargeted metabolite profiling was conducted on serum samples. Results IF significantly reduced weight gain, fat mass and liver weight, improved glucose tolerance and insulin sensitivity in middle-aged mice fed with high-fat diet. 16 S rRNA gene sequencing revealed that IF significantly reduced the Firmicutes/Bacteroidetes (F/B) ratio by increased Muribaculaceae, Bacteroides, Parabacteroides, and decreased Bilophila, Colidextribacter, Oscillibacter. The serum untargeted metabolomics revealed that IF could modulate differential metabolites and metabolic pathways associated with glycolipid metabolism. Spearman’s correlation analysis indicated that key differential microbiota were strongly correlated with glucose metabolism-related indicators and serum metabolites such as stearic acid, obeticholic acid, and N-acetylglycine. Conclusions IF improves glucose metabolism, regulates gut microbiota, and alters serum metabolites in middle-aged mice fed a high-fat diet. This provides a new pathway for trials testing diabetes prevention in middle-aged and elderly patients.